Minimizing Oxidation of Freeze-Dried Monoclonal Antibodies in Polymeric Vials Using a Smart Packaging Approach - Nicole Härdter; Tim Menzen; Gerhard Winter (MDPI AG, 2021)
Primary containers made of cyclic olefin polymer (COP) have recently gained attention since they may overcome several risks and shortcomings of glass containers as they exhibit a high break resistance, biocompatibility, and homogeneous heat transfer during lyophilization. On the downside, COP is more permeable for gases, which can lead to an ingress of oxygen into the container over time. Since oxidation is an important degradation pathway for monoclonal antibodies (mAbs), the continuous migration of oxygen into drug product containers should be avoided overall. To date, no long-term stability studies regarding lyophilizates in polymer vials have been published, potentially because of the unbearable gas permeability. In this study, we demonstrate that after lyophilization in COP vials and storage of these vials in aluminum pouches together with combined oxygen and moisture absorbers ("smart packaging"), oxidation of two lyophilized therapeutic antibodies was as low as in glass vials due to the deoxygenated environment in the pouch. Nevertheless, active removal of oxygen from the primary container below the initial level over time during storage in such "smart" secondary packaging was not achieved. Furthermore, residual moisture was controlled. Overall, the smart packaging reveals a promising approach for long-term stability of biopharmaceuticals; in addition to COP's known benefits, stable, low oxygen and moisture levels as well as the protection from light and cushioning against mechanical shock by the secondary packaging preserve the sensitive products very well.